A Latent Class Analysis of Spanish Travelers' Mobile Internet Usage in Travel Planning and Execution. (May 2015) - Okazaki, Shintaro; Campo, Sara; Andreu, Luisa; Romero, Jaime
A study of 476 Spanish travelers found mixed interest and use for the many travel-related mobile internet services that are involved in planning and executing a trip. The findings indicate that these Spanish respondents can be classified into four segments based on the timing of using mobile apps for over a dozen activities involved in travel planning and execution: Savvies, Planners, Opportunists, and Low-techs . Each segment exhibits distinct patterns of mobile internet services usage. Savvies tend to be heavy mobile device users both before and during their trip, while Planners make heavy use of mobile devices in advance of but not during their trip. The Opportunists show a pattern opposite the Planners, and fire up their phones and pads when they arrive at a destination. Low-techs generally do not participate in the mobile internet. The respondents generally saw four benefits from mobile device use: ubiquity, immediacy, personalization, and information access, but the four groups ranked those benefits differently.